Analysis of Factors that Increase Customer Satisfaction Coffee Products - Suryawardana, Edy; Nurdeagraha, Doni (Journal of Digital Marketing and Halal Industry, 2020)
Satisfaction is the level of feeling where someone states the comparison of the product's performance (service) received and expected. This study aimed to determine the effect of price, service quality, product quality, product diversity, promotion, and location on customer satisfaction. This study uses a quantitative approach. The sample is the consumer "P" Coffe Gajahmada Semarang branch. The sampling technique used purposive sampling—sources of data were obtained through the distribution of closed-question questionnaires. The data analysis technique used multiple linear regression analysis. Hypothesis test results show that price, service quality, product quality, product diversity, promotion, and location have a positive and significant effect because all independent variables have a significant probability value 0.05. The coefficient of determination showed 0.845 or 84.5%. It is necessary to increase product diversity in the form of completeness, brand, and variety in the future.